Mentorship Siswa dalam Melatih Kemampuan Bahasa Inggris Berbasis Immersion - Ozi Satria; Bakri, Umar; Rijnan (Indonesia, 2024)
In this globalization era, teachers have to provide mesmerizing method or strategy in order to have brilliant way of teaching and learning process. Therefore, this research and community outreach (PKM) was aimed to assist mentoring about developing students’ English language particularly speaking skill for the students of MTs. Nurul Islah Beleka. This activity was intended to increase students’ motivation in relation to learning English well. Not only is that but a mesmerizing method or strategy also will be more effective to make higher quality of students’ comprehension especially their speaking skill by using Immersion as a method. The PKM team did four steps such as planning, action. Closing activity, and evaluating activity. The result of this research and community outreach (PKM) was based on Brown (2001) that there are 7 indicators which indicates the quality of students’ speaking skill but only 6 indicators that the students reach for instances they were able to add their vocabulary, arrange their grammar, speak fluently, speak with good pronunciation, indicating a comprehension, and also they are capable to produce high quality of intonation. Those result above, was the outcome of using the Immersion strategy.